Impact of Planning on Quality Implementation of Engineering Projects Case Study: Koya District, Hawler Provence – Kurdistan Region of Iraq - Ali, Peshawa J. Muhammad; Taha, Bahman Omar; Faraj, Rezhna Hassan (Sulaimani Journal for Engineering Sciences, 2016)
Project success means different things to different peoples, public projects are services of general interest which grabs the attention of most of citizens. Infrastructure of cities, public buildings and road must be implemented according to a plan set by city council or city authorities and then to be implemented by engineering directorates. Project success is a complicated process has economic, environmental, political and social trends. Success of project measured through proper planning, cost, quality, functionality, and on time completion. In order to show the consequences of poor and faulty project planning, a number of unfinished, badly finished and/or deserted construction projects have been thoroughly analyzed. Accordingly, 20 constructional public service projects are considered. The included area of the study covers Koya district in Kurdistan-Iraq (36.084643N, 44.627252E) while the time span of the study extends to thirteen years, including projects started in January 2000. A questionnaire form is distributed among 50 experts living in the Koya district itself. Experts are professionals in different sectors relating to construction, management and planning. They are asked for their openion about the success of these projects as well as the reason of failure if exist. For this purpose seven predefined casues of failure were specified by authors. Results showed that the main reason for failure is lack of planning, and the most common secondary reason for failure is the functionality problem (project not function well for some reason). This research concluded that lack of a unified perspective for the future of the district, and the absence of long-term city master plan are the main reasons behind poor planning and implementation of the projects.
Keywords: Koya; planning; project success